Physio-mechanical simulation of human's left ventricle using finite element method - Chen, Qiang (2008)
Heart diseases are the leading causes of death worldwide and most of these diseases happen in left ventricle (LV). The modeling LV muscle is crucially important as cardiac muscle is the main component of ventricle wall. In this thesis, based on physiological observation, LV muscle is assumed to be composed of two different materials: myocardium masses (MM) and myocardium fibers (MF). An isotropic Mooney-Rivlin material property is implanted into MM, and a Hill’s fiber force model is developed for representing MF which relates the microscopic molecular electricity events to macroscopic LV muscle performance. This assumption simply but effectively implants real complex fiber structure into the LV model. The fluid-structure interaction between MM and cavity blood (CB) has been considered using penalty method. The mathematical model has been discretised into numerical model using finite element method (FEM). MM and MF are meshed by finite element, while CB is meshed by an Arbitrary Lagrangian Eulerian (ALE) finite element. The available FEM package LS-DYNA is used as the solver. The FEM results show good agreements with clinic report and other references. The model can be a powerful tool to diagnose cardiac abnormities in future studies.